Creating a Blueprint for a Critical Social Pedagogy of Learning for Life and Work: Canadian Perspectives - André P. Grace (Adult Education Research Conference, 2006)
In Canada, current federal learning-and-work policy is focused on individual learner-worker development using an iteration of lifelong learning as cyclical. Increasing numbers of disenfranchised young adults are resisting participation in such learning. In this regard, I consider the predicament of young adults in the Canadian province of Newfoundland and Labrador. To help us think about adequately addressing the dislocation they experience in life and work, I offer a Freire-informed vision of a critical social pedagogy of learning and work.
Keywords: Cyclical lifelong learning; critical social pedagogy; learner participation